2020
DOI: 10.1002/jum.15589
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between SonoVue and Sonazoid Contrast‐Enhanced Ultrasound in Characterization of Focal Nodular Hyperplasia Smaller Than 3 cm

Abstract: Objectives This study aimed to compare the diagnostic efficacy of contrast‐enhanced ultrasound (CEUS), including SonoVue (SV; sulfur hexafluoride; Bracco SpA, Milan, Italy) and Sonazoid (SZ; perflubutane; GE Healthcare, Oslo, Norway), and explore the differences between them in the characterization of CEUS features in focal nodular hyperplasia (FNH) smaller than 3 cm. Methods This retrospective study included 31 lesions smaller than 3 cm diagnosed as FNH by CEUS between April 2019 and November 2019. Nine patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The results indicated that there was no correlation between the tumor necrosis and MVI (Zhu et al 2017). However, previous studies reported that SZ-CEUS has the potential ability to visualize a central necrosis compared with SV-CEUS ( He et al 2021), and the contrast defect from the center might mimic a central necrosis, which could also be seen on other focal lesions (Rousseau et al 2015). Hence, we hypothesize that the difference in results was due to the different UCA.…”
Section: Discussionmentioning
confidence: 83%
“…The results indicated that there was no correlation between the tumor necrosis and MVI (Zhu et al 2017). However, previous studies reported that SZ-CEUS has the potential ability to visualize a central necrosis compared with SV-CEUS ( He et al 2021), and the contrast defect from the center might mimic a central necrosis, which could also be seen on other focal lesions (Rousseau et al 2015). Hence, we hypothesize that the difference in results was due to the different UCA.…”
Section: Discussionmentioning
confidence: 83%
“…To date, Sonazoid has been commercially available only in China, Japan, Korea and Norway. A few studies 23,24 have shown that the diagnostic performances of the two contrast media are comparable in terms of accuracy and safety. More specifically, Zhai et al 23.…”
Section: Discussionmentioning
confidence: 99%
“…23 To date, Sonazoid has been commercially available only in China, Japan, Korea and Norway. A few studies 23,24 have shown that the diagnostic performances of the two contrast media are comparable in terms of accuracy and safety. More specifically, Zhai et al23 reported sensitivity and specificity values of 84.6% and 95%, respectively, in detecting hepatocarcinoma when Sonazoid was used and 83.3% and 95%, respectively, when SonoVue was administered.…”
Section: F I G U R Ementioning
confidence: 99%
“…And SLN can be detected at least 1 h after SNZ injection, 35 while SNV is only 5 min. 32 Therefore, SNZ has more advantages in assessing the situation after LN resection.…”
Section: Magnetic Tracer Methodsmentioning
confidence: 95%
“… 34 In addition, Sonazoid is relatively stable and has a high rate of phagocytosis by Kupffer cells in vitro (99.00%). And SLN can be detected at least 1 h after SNZ injection, 35 while SNV is only 5 min 32 . Therefore, SNZ has more advantages in assessing the situation after LN resection.…”
Section: Trans‐lymphatic Contrast‐enhanced Ultrasound (Tlceus)mentioning
confidence: 99%